(untitled) (LEARNing Landscapes, 2008)
This article focuses upon the significance of art experiences at moments of pervasive unease and uncertainty in the society surrounding the schools. Concerned more with a loss of expectation and a sense of futility than actual fear of catastrophe, I turn towards encounters with the several arts to activate imagination which, as Emily Dickinson wrote, may "light the slow fuse of possibility." The sense of possibility, of what might be, what ought to be, what is not yet–seems to be essential in moving the young to learn to learn. It may be nurtured, not only through art education as ordinarily understood, but also through aesthetic education, moving people by means of participation, to awaken to the wonders of authentic appreciation.